Introducing National Health Accounts in Albania - Osmat Azzam; Sotiraq Dhamo; Tonin Kola (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2005)
The health sector is defined as the priority sector in the Albanian Strategy for the social and economic development. The Albanian Health sector is in the continuing transformation in the function of the realization of the proper standards. To realize the reform in this sector and to help the decision makers in their decision is necessary to have the right information on the source of the financing of health sector, on the destination of the expenditure in this sector and their control. Preparing the NHA in accordance with the International Standards in this field, should do possible and the comparability of the performance of the indicators of health sector with them of other country, so that the Albanian authorities and International organization which support the development of this sector in Albania, for the proper definition of the way and the funds necessary to develop this sector in Albania. In this paper has been evidenced the actual problems of the development of the Health sector in Albania and are given some recommendation for the preparing of the NHA in Albania. The main recommendation include the necessity to build a technical body to collect and analyze data, to have an "steering committee" to interprets the results in terms of the policy implications, and refers of this results to the legislative body to enact and implement a policy in health sector development.
Keywords: 330; Gesundheitsstatistik; Statistische Methode; Gesundheitsfinanzierung; Albanien